Risk factors evaluation of cerebral palsy in Hazara division KPK Pakistan: A cross-sectional survey - Keramat, Keramat Ullah; Muhammad Athar Khalily; Abdul Haseeb Bhutta; Pirzada Khattak; Anam Habib; Nimra Ilyas Bhutta (Journal of the Pakistan Medical Association, 2022)
Objectives: To evaluate the prevalence of risk factors of cerebral palsy in the mothers of children with cerebral palsy. Method: The cross-sectional study was conducted in 2018 at the Helping Hand Institute of Rehabilitation Sciences, Mansehra, Pakistan, and comprised mothers of cerebral palsy children aged 1-18 years from the Hazara Division. Data was collected using a modified form of Surveillance of cerebral palsy in Europe questionnaire regarding prenatal, natal and postal natal risk factors. Data was analysed using SPSS 21. Results: Of the 300 children, 190(63.3%) were males and 110(36.7%) were females. The mean (±SD) age of the children was 5.43±3.63 years and that of their mothers at the time of delivery was 26.16±5.11 years. Among the prenatal risk factors, anaemia was the leading factor 179(59.6%), while delayed crying 187(63.3%) was the major postnatal factor. Consanguinity was reported by 200(66.7%) mothers. Majority of the deliveries 201(67%) had taken place at hospitals. Conclusion: Anaemia and delayed crying were the major risk factors identified in mothers and children, respectively, in the study sample. Key Words: Cerebral Palsy, Anti-natal risk factors, Postnatal risk factors, SCPE.